PENETAPAN STRUKTUR MODAL YANG OPTIMAL DALAM UPAYA MENINGKATKAN NILAI PERUSAHAAN - Dita Priesti Amaniah; . Suhadak; R. Rustam Hidayat (Jurnal Administrasi Bisnis, 2013)
The research aim to understand the company’s policy in determining capital structure, understand the optimal capital structure in the effort of improving company’s value, and to understand the effect of optimal capital structure against the company’s value. The result of this study indicates that the capital structure strategy of PT. Indofood Tbk tends to employ larger amounts of equity compared to its debt capital. Optimal capital structure of the three observations occurred in 2011 is when the company’s calculation of a minimum average cost and a maximum value. The highest value of the Company occurred in 2011 was when the company used its own sources of funding and larger equity and when the cost of capital at the company’s calculated average minimum.   Keywords: Optimal Capital Structure, Company Value